Assistance for Santri-Friendly Islamic Boarding School (Bullying and Sexual Violence Free) at Al-Amin Islamic Boarding School Mojokerto - Muhammad Farid Ilhamuddin; Ahmad Abdullah Zawawi; Lutfi Saksono; Ainur Rifqi (Center for Community Service and Science and Technology Marketing - The Institute for Research and Community Service Universitas Negeri Surabaya, 2025)
The rise of bullying and violence in Islamic boarding schools, especially in the Mojokerto area, shows the need for more effective prevention efforts. Although some Islamic boarding schools have implemented character learning and internal policies, specific steps to protect students are still limited. This problem is the background for the emergence of a student-friendly Islamic boarding school mentoring program at the Al-Amin Islamic Boarding School in Mojokerto. The implementation of the service program at the Al-Amin Islamic Boarding School in Mojokerto is carried out through three stages, namely preparation, implementation, and evaluation. The data collection method was carried out by a mixed method which included participatory observation, structured interviews, documentation, and questionnaires, with the main focus on preventing bullying and sexual violence, establishing student-friendly Islamic boarding school and increasing the capacity of administrators, caregivers, and ustaz/ustazah. The